Revealing the pH-dependent mechanism of nitrate electrochemical reduction to ammonia on single-atom catalysts. Issue 41 (11th October 2022) - Yan, Jingjing; Xu, Haoxiang; Chang, Le; Lin, Aijun; Cheng, Daojian
Abstract : Nitrate electrochemical reduction to ammonia (NO3 RR) catalyzed by single-atom catalysts (SACs) is an attractive and efficient way of solving the problem of nitrate pollution in water and obtaining valuable product ammonia through low temperature synthesis. Abstract : Nitrate electrochemical reduction to ammonia (NO3 RR) catalyzed by single-atom catalysts (SACs) is an attractive and efficient way for solving the problem of nitrate pollution in water and obtaining valuable product ammonia through low temperature synthesis. It is well known that the pH conditions can be regulated to tune the performance of NO3 RR, however, there have been few studies aimed at gaining theoretical insight into the origin of pH-dependent catalytic performance among SACs. Herein, taking 3d-transition metal (Fe, Co, Ni and Mn) single-atoms supported on diverse anchor sites of MoS2 as an example (SA-MoS2 ), we explore the activity and selectivity for NO3 RR towards ammonia (NH3 and NH4 + ) under different pH conditions by density functional theory calculations. It is found that priority reaction pathways, the potential determining step and limiting potentials of SA-MoS2 exhibit pH-dependent characteristics, which can be described by a contour map of catalytic reactivity, spanned by adsorption free energies ( G NO* and G NH2 * ), and further determined by local coordination environment and electronic states of active sites. Our three-step screening method reveals that the Co single-atom adsorbed MoS2 edge catalyst is the most promising catalyst among the studied SA-MoS2 because of its low limiting potential (−0.3–0.4 V, RHE), excellent selectivity in the competition with the hydrogen evolution reaction (HER), as well as stability against aggregation and electrochemical dissolution across the full pH range. This work demonstrates a theoretical insight into the pH-dependent mechanism of supported SA catalyzed NO3 RR, which proposes a screening strategy for finding new SACs, and provides motivation for further experimental exploration.